Facility Location Modeling in Multi-Echelon Distribution System: A Case Study of Indonesian Liquefied Petroleum Gas Supply Chain - Ilyas Masudin (Aceh International Journal of Science and Technology, 2013)
Abstract -This paper presents model of Indonesian LPG supply chain by opening new facilities (new echelon) taking into account the current facilities. The objective is to investigate the relation between distribution costs such as transportation, inventory cost and facility location in Indonesian multi-echelon LPG supply chain. Fixed-charged capacitated facility location problem is used to determine the optimal solution of the proposed model. In the sensitivity analysis, it is reported that the trade-offs between facility locations and distribution costs are exist. Results report that as the number of facility increases, total transportation and inventory cost also increase.Keywords: LPG supply, location, inventory, transportation